2013
DOI: 10.1039/c3cp42648c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of chemically pure, luminescent Eu3+ doped HAp nanoparticles: a promising fluorescent probe for in vivo imaging applications

Abstract: The poor solubility, poor biocompatibility and disposal issues make fluorescent quantum dots such as CdSe, CdS, ZnS, InP, InAs, etc. impractical for imaging tissues or intercellular structures. As calcium phosphate is the main inorganic component of human bone and teeth, hydroxyapatite (Ca10(PO4)6(OH)2, HAp) is highly biocompatible and bioactive. Since HAp nanoparticles are not luminescent, a novel inorganic biocompatible fluorescent probe was suggested by doping HAp with lanthanides. Here we report the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Additionally, HAp could be a good host material for lanthanide doping by substitution of Ca 2+ with lanthanide ions into the HAp crystal lattice [7, 12]. The lanthanide doped HAp may endow the particles with fluorescent properties, which can overcome low fluorescence intensity and low photostability of traditional fluorescence dyes, and avoid toxicity and disposal issues of quantum dot probes [13]. It has been reported that lanthanide ions, such as europium and terbium, exhibited the typical fluorescence for cell imaging under the specific excitation wavelength [7, 12, 13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, HAp could be a good host material for lanthanide doping by substitution of Ca 2+ with lanthanide ions into the HAp crystal lattice [7, 12]. The lanthanide doped HAp may endow the particles with fluorescent properties, which can overcome low fluorescence intensity and low photostability of traditional fluorescence dyes, and avoid toxicity and disposal issues of quantum dot probes [13]. It has been reported that lanthanide ions, such as europium and terbium, exhibited the typical fluorescence for cell imaging under the specific excitation wavelength [7, 12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…The lanthanide doped HAp may endow the particles with fluorescent properties, which can overcome low fluorescence intensity and low photostability of traditional fluorescence dyes, and avoid toxicity and disposal issues of quantum dot probes [13]. It has been reported that lanthanide ions, such as europium and terbium, exhibited the typical fluorescence for cell imaging under the specific excitation wavelength [7, 12, 13]. In particular, doping of europium, which has 4 f-4 f intraorbital electronic transitions spanning the visible and near-infrared ranges, leads to an important material for biomedical applications in the near-infrared spectral range [11, 14].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of luminescent or fluorescent capabilities to a calcium phosphate nanomaterial drug delivery system will further enhance their in vivo functionality. For this reason, investigations have begun to examine the possibility of conjugating QDs with calcium phosphate nanoparticles and nanowhiskers in addition to doping it with elements such as lanthanide and cyanine dyes such as indocyanine green in an effort to improve biocompatibility and to achieve elimination of cytotoxicity within a physiological environment [46][47][48][49][50][51][52][53][54]. Although most work is carried out on nanoparticles, the same approach could be used in nanocoatings.…”
Section: Recent Advances In Calcium Phosphate Nanomaterials In Bioimamentioning
confidence: 97%
“…In comparison with organic dyes, the stability of fluorescent nanoparticles such as QDs in biological systems makes them a constant research interest as biological probes in diagnostic or targeted therapeutic applica- Calcium phosphate nanocoatings & nanocomposites, Part I Review tions [46]. However, issues such as biocompatibility as well as their short-term and long-term toxicity inside the human body due to the use of heavy metal such as cadmium during the fabrication of QDs needs to be addressed before their widespread use in applications such as cancer imaging and sentinel lymph-node mapping [45].…”
Section: Recent Advances In Calcium Phosphate Nanomaterials In Bioimamentioning
confidence: 99%
“…In addition, the feasibility of rendering HANPs fluorescent and also magnetically active opens many possibilities in imaging and therapy, e.g. tumor ablation [4,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%